ANALISIS PRESTASI TURBIN GT-1510 BORSIG PADA UNIT UTILITY KALTIM I - Basri, Muhammad Hasan; Sam, Alimuddin (MEKTEK, 2006)
This research aim to analyses how far labour capacity or performance from GT-1510 Borsig turbine in Kaltim-1 utility unit. From the analysis can such component to prediction from turbine of degradation of performance so that requaire to conducted action by turbine component replacement or treatment and also is when done by overhaul.